Cambridge international AS level history - Wadsworth, Phil (Cambridge University Press, 2014)
Sample Scheme of Work helps in the overall planning of the course. Additional guidance on the specification, assessment and skills makes syllabus information relevant and clear. Teaching ideas offer help with lesson planning. Worksheets with associated answers provide help in preparing and setting homework. Revision handouts help in preparing students for exams and revision. Answers to all questions in the coursebook saves teachers precious time. Exemplar exam questions offer support to teachers to help their students to attain highly.